Asuhan Keperawatan Pada Ny.E dengan Post Partum Spontan di Ruang Anyelir RSUD Banyudono - Lestari, Sri Puji, Rina Ambarwati, S.Kep., Ns (2013)
Background: Post partum be one of the cause from death several mothers died, because mother post partum want more attention in birthing time finished until 6 weeks or 42 days. Childbed time is critical time after give birth to. One of the woman quantity cause dieds from a inattentive cause in woman post partum Objective: To knowing nursing care to patients with normal post partum include assessment, intervention, implementation, and evaluation of nursing. Results: After adjusting for 2x8 hour nursing actions obtained signs of infection disappeared, the mobility of the patient are met without any help, improved patient knowledge about breast care. Conclusion : After carried out for nursing performances, studying, data analyzing, concluding the diagnosis, planning about the action, and evaluating to Mrs. E with post partum or menstruation periods has been encountering well.